2022
DOI: 10.1002/jper.22-0322
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis prevalence and severity in inflammatory bowel disease: A case–control study

Abstract: Background: Recent evidence is supporting the notion of a microbiological and immunological continuum on the gum-gut axis in health and disease. Therefore, the purpose of this study was to assess the prevalence and risk indicators of periodontitis in patients with Crohn's disease (CD) or ulcerative colitis (UC) compared to age-and sex-matched controls without inflammatory bowel disease (IBD). Methods: A total of 180 IBD (117 CD, 60 UC, 3 IBD-unclassified) and 180 healthy controls were compared for their period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…A recent study using the full-mouth clinical periodontal assessment in a large group of patients established a relationship between IBD severity and periodontal diseases 40 . According to Kitamoto et al periodontal disease, aggravates gut inflammation by supplying the gut with both colitogenic pathobionts and pathogenic T cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using the full-mouth clinical periodontal assessment in a large group of patients established a relationship between IBD severity and periodontal diseases 40 . According to Kitamoto et al periodontal disease, aggravates gut inflammation by supplying the gut with both colitogenic pathobionts and pathogenic T cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Differences were more pronounced in the 35-to 50-year-old and 51-to 65-yearold age groups, but there were no significant differences between CD and UC. 26 However, in contrast, a casecontrol study asserted that IBD was not related to worsening periodontal diseases, indicating that IBD did not necessarily enhance susceptibility to periodontitis. 27 Factors such as the elderly age group, and smoking status, were found to have greater odds of developing periodontitis and its severity in IBD patients.…”
Section: Prevalence and Risk Of Periodontal Disease In Ibd Patientsmentioning
confidence: 96%
“…In contrast, other researchers observed higher values of plaque indices in IBD patients but no significant differences in caries and periodontal status between the study and control groups [ 20 ]. However, in the most recent studies from 2022, the authors found that the progression of periodontitis is closely associated with a worsening of the course of IBD [ 21 , 22 ]. Therefore, preventive and therapeutic strategies concerning the oral–gut axis should be imposed in IBD patients.…”
Section: Oral Health Status In Patients With Inflammatory Bowel Disea...mentioning
confidence: 99%